Cardiovascular Autonomic Dysfunction Is the Most Common Cause of Syncope in Paced Patients - Yasa, Ekrem; Ricci, Fabrizio; Holm, Hannes; Persson, Torbjörn; Melander, Olle; Sutton, Richard; Fedorowski, Artur; Hamrefors, Viktor (Frontiers in Cardiovascular Medicine, 2019)
Introduction: Syncope and orthostatic intolerance in paced patients constitute a common clinical dilemma. We, thus, aimed to determine the aetiology of syncope and/or symptoms of orthostatic intolerance in paced patients. Methods: Among 1705 patients with unexplained syncope and/or orthostatic intolerance that were investigated by cardiovascular autonomic tests, including Valsalva manoeuvre, active standing, carotid sinus massage, and tilt-testing, 39 patients (2.3 %; age 65.6 years; 39 % women) had a cardiac implantable electronic device (CIED). We explored past medical history, diagnoses found during cardiovascular autonomic tests, and the further clinical workup, in case of negative initial evaluation. Results: An aetiology was identified during cardiovascular autonomic tests in 36 of the 39 patients. Orthostatic hypotension (n=16; 41%) and vasovagal syncope (n=12; 31%) were the most common diagnoses. There were no cases of pacemaker dysfunction. The original pacing indications followed guidelines (sick-sinus-syndrome in 16, atrioventricular block in 16, atrial fibrillation with bradycardia in five). Twenty-two of the 39 patients (56 %) had experienced syncope prior to the original CIED implantation. Orthostatic hypotension was diagnosed in seven (32%) and vasovagal syncope in nine (41%) of these patients. Of the 17 patients that had not experienced syncope prior to the original CIED implantation, nine patients (53 %) were diagnosed with orthostatic hypotension and vasovagal syncope was diagnosed in three (18%). Of the 39 patients, two had implantable cardioverter-defibrillators to treat malignant ventricular arrhythmias diagnosed after syncopal episodes. Conclusion: Cardiovascular autonomic tests reveal the aetiology of syncope and/or orthostatic intolerance in the majority of paced patients. The most common diagnosis was orthostatic hypotension (40 %) followed by vasovagal syncope (30%), whereas there were no cases of pacemaker dysfunction. Our results emphasize the importance of a complete diagnostic work-up, including cardiovascular autonomic tests, in paced patients that present with syncope and/or orthostatic intolerance.